PREFERENSI PROFESI SEBAGAI AKUNTAN PUBLIK DAN NON AKUNTAN PUBLIK DITINJAU DARI TIPE KEPRIBADIAN MAHASISWA AKUNTANSI - Riska Fajrin (Jurnal Ilmiah Mahasiswa FEB, 2015)
The study discusses students’ preferences upon public and non-public accountant professions based on their personality types. The aim of this qualitative research is to describe how students of the Accounting Department prefer their profession in terms of the personality type that they consider for pursuing the desired job. The data were obtained through interviews and personality tests occupying Self-Directed Search (SDS) instrument from the theory of Holland. The result of this study shows that the students viewed preference an important issue for the selection of their profession. The six personality types as proposed by the theory have their own opinion; yet, they share the same perspective. Regardless the distinctive personality possessed, the accounting students in general prefer accountants as their major profession. Key words: Preferences; Profession; Public accountant; Non-public accountant; Personality type.